Strategi Penanaman Nilai Spiritual dan Perilaku Sosial Siswa Melalui Pembelajaran di SDIT Rahmaniyah - lestari, iis dewi lestari; Brahma, Ismail Akbar; Halimatusha’diah, Halimatusha’diah; Putri, Laksita Nirmala; Sulistyaniningsih, Endang (UIR Press, 2025)
The purpose of this study is to examine the strategies implemented by SDIT Rahmaniyah in instilling spiritual values and social behavior in students through learning activities. This research employs a qualitative descriptive method. Data analysis techniques include data collection, reduction, presentation, and drawing conclusions. The data collection techniques used are observation, interviews, and documentation.The results of the study show that SDIT Rahmaniyah applies habituation strategies in daily activities and carries out programs and activities to instill spiritual values, such as congregational Duha prayer and collective supplication. In addition, the school incorporates a special Qur'an learning method with Qur'an teachers. SDIT Rahmaniyah also organizes Islamic-themed competitions such as Qur'an memorization contests, Qur'an recitation, and Islamic fashion shows.The conclusion of this study is that the strategy for instilling spiritual and social values at SDIT Rahmaniyah includes integrating spiritual values into learning—such as incorporating values of faith, piety, and noble character; implementing daily habituation of spiritual values within learning activities; and utilizing cooperative and problem-based learning methods by teachers to instill these values.